2015
DOI: 10.1542/peds.2014-2955
|View full text |Cite
|
Sign up to set email alerts
|

Medical-Legal Strategies to Improve Infant Health Care: A Randomized Trial

Abstract: BACKGROUND: Changes in health care delivery create opportunities to improve systems to better meet the needs of low-income families while achieving quality benchmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
123
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 46 publications
1
123
0
2
Order By: Relevance
“…Similar to the child health measures, there were no statistically significant differences at follow-up in caregiver general health, depression symptoms, or perceived stress between intervention groups with or without adjustment (Table 3) endorsed by major professional organizations. 66,67 There have been several other trials in pediatric settings that examine the effectiveness of multidomain social risk screening and interventions, [22][23][24] although we are aware of only 1 that has included an intervention limited to providing written social resource information. 25 In this randomized clinical trial, the lack of significantly greater benefit when adding longitudinal, in-person navigator services to the delivery of written social resources information was unexpected, given that an earlier trial in this area 25 found significant differences between groups.…”
Section: Change In Caregiver Healthmentioning
confidence: 99%
“…Similar to the child health measures, there were no statistically significant differences at follow-up in caregiver general health, depression symptoms, or perceived stress between intervention groups with or without adjustment (Table 3) endorsed by major professional organizations. 66,67 There have been several other trials in pediatric settings that examine the effectiveness of multidomain social risk screening and interventions, [22][23][24] although we are aware of only 1 that has included an intervention limited to providing written social resource information. 25 In this randomized clinical trial, the lack of significantly greater benefit when adding longitudinal, in-person navigator services to the delivery of written social resources information was unexpected, given that an earlier trial in this area 25 found significant differences between groups.…”
Section: Change In Caregiver Healthmentioning
confidence: 99%
“…HMH as a measure of poverty is appealing in the context of systematic clinical screening as it is both associated with child health outcomes, and remediable with clinic‐based intervention . HMH is widely prevalent in the United States—nearly one in five US children lives in a food insecure home—and primary care data demonstrate that linking families with HMH with targeted “safety‐net” programs (e.g., food stamps or food banks) can improve child outcomes . To date, only a single small research study has explored the feasibility of poverty screening in pediatric oncology .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] HMH is widely prevalent in the United Statesnearly one in five US children lives in a food insecure home-and primary care data demonstrate that linking families with HMH with targeted "safety-net" programs (e.g., food stamps or food banks) can improve child outcomes. 11,22 To date, only a single small research study has explored the feasibility of poverty screening in pediatric oncology. 23 Potential barriers to systematic screening include both parental reluctance to participate, as well as challenges with adequate staffing to perform and respond to such screening.…”
Section: Introductionmentioning
confidence: 99%
“…A venue committed to being a medical home for children and young adults should seek broadly innovative ways of improving health outcomes for children in its practice and can also consider extending its efforts to the greater pediatric community. 35,36 Payers should value and encourage research and initiatives that are likely to elevate health outcome trajectories over the longterm. 37 Continuous real-time sharing of data about patient populations between payers and practices can be a powerful way to help both groups respond to health needs in a timely way.…”
Section: Improving the Health Of The Populationmentioning
confidence: 99%